Analysis Of Moves and Tenses on Abstract Article Published at Journals - Hendra Putra (ETERNAL (English Teaching Journal), 2023)
An abstract has an important role in the research article. Generally, if the researcher wants to submit the article the first thing that must be done is to submit an abstract. This article aims to identify the moving structure of English abstracts of researcher’s articles from many sources that were published started from 2011 to 2021, to identify of applying tense and disagreement of subject and tense in writing abstract article. This study employed a genre analysis approach. As data collection techniques are used 10 abstract articles from the journal were published and then analyzed by using a moving structure from Hyland and Swales & Feak. The result can be revealed that they are 7 abstract articles that applied the introduction, 9 abstract articles that applied purpose, 9 articles that applied method, and 10 abstract articles that applied product move then there are 4 abstract articles applied conclusion move. In applying tense, the most used is simple present tense. It can be concluded that the most applied move is the product in writing an abstract article then the most used tense is in the simple present tense in writing an abstract article.